Bridging Islamic juristic differences in contemporary Islamic finance. - Soualhi, Younes (IIUM Press, 2011)
The research is an attempt to fonnulate a viable shariah framework for juristic differences in contemporary Islamic finance. While acknowledging the legitimacy ofjuristic differences as an inherent feature ofIslamic law, the same differences could jeopardize a nascent Islamic finance industry, leading to what has come to be arbitrarily tenned shariah risk in Islamic finance. Two blocks seem to represent the two disputing sides ever since this industry was launched, i.e:, the Middle East and South East Asia markets. Thus, this research aims at bridging differences in Islamic finance by proposing a frame work and a set of parameters that can be applied in all products of Islamic banking, Islamic Capital Market and Takaful. Apart from the outlined framework that aims to get out of juristic disputes, the research concluded that no juristic dispute resolution in Islamic finance is attainable without appreciating the legal and regulatory differences in which Islamic finance operates across the globe.